An Enhanced Multidimensional Security Framework for Securing PaaS-Based E-Commerce Cloud Environments - Savita Singh,; Dr. Vijay Mohan Shrimal, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2026)
The fast movement to cloud computing has made Platform-as-a-Service (PaaS) one of the most significant enablers of the scalable and agile E-commerce applications. Nevertheless, PaaS environments pose serious security issues because of multi-tenancy, dynamic workloads, shared service elements, and high-performance demands. Traditional security strategies tend to respond to isolated threats and do not weigh the security performance with the operational performance. The given paper offers to introduce the Enhanced Multidimensional Security Framework (PaaS-MSF) that should be used in order to protect the PaaS-based E-commerce cloud environment and maintain the sustainability of its performance. The suggested framework will incorporate several security aspects such as identity and access control, context-wary risk determination, intrusion detection and response, tenant isolation, compliance monitoring, and performance-conscious enforcement in one architecture. A multi-phase developmental evaluation approach is embraced and integrates organizational survey analysis, stochastic security simulation on StochSS, cloud performance modelling on CloudSim Automation and statistical validation on SPSS. This will allow experimental and reproducible testing under baseline and more secure settings. As it is evidenced by experimental outcomes, the suggested framework is much better at detecting intrusions, preventing them, and containing threats than traditional PaaS security frameworks. Notably, these security improvements are made with less effect on critical performance indicators like response time, throughput and resource usage. The results indicate that context sensitive and adaptive security enforcement are capable of addressing threats with respect to E-commerce without bringing about unacceptable performance burden. Altogether, this research brings a validated, performance-conscious, and standards-oriented security framework that will further theoretical and practical knowledge on the topic of PaaS security. The suggested solution is an informative resource to cloud service providers, E-commerce platforms, and security practitioners who might need to improve the security resilience of their environment in the current cloud setting.